REVISITING THE HADITH ON WOMEN ATTENDING FUNERALS: MAQASID AL-SHARIAH, CONTEXTUAL INTERPRETATION, AND THE EVOLUTION OF JURISTIC IJTIHAD - Fauziah, Ulya; Hasyim, Ahmad Faqih; Umayah, Umayah (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
The participation of women in funeral rites has long been a subject of juridical debate in Islamic scholarship, particularly in relation to the hadith narrated by Ummu ‘Aṭiyyah which mentions a prohibition on women following funeral processions. This study investigates the normative meaning and legal intent of the hadith by integrating hadith criticism with a maqāṣid al-sharī‘ah approach, as conceptualized by Imam al-Shāṭibī. Using qualitative library research, this article examines the transmission routes of the hadith, its linguistic formulation, and the interpretations offered by classical commentators and contemporary jurists. The study finds that the hadith is transmitted through authentic and continuous chains and is categorized as hadith ahad. Although its wording appears non-explicit in attributing the prohibition directly to the Prophet, the dominant scholarly position considers it marfū‘ due to established principles in hadith methodology. From a maqāṣid-oriented perspective, the prohibition is not intended as a permanent legal restriction but as a contextual measure aimed at preventing potential harm, particularly in safeguarding emotional stability and rational judgment during funeral rituals. These objectives correspond to the preservation of essential human interests, especially the protection of life (hifz al-nafs) and intellect (hifz al-aql). Accordingly, the study concludes that the legal ruling concerning women attending funerals is best understood as advisory rather than absolute, falling within the category of discouragement rather than prohibition. In contemporary settings where social norms and emotional discipline differ significantly from earlier contexts, women’s participation in funeral rites may be permissible, provided that Islamic ethical guidelines are observed. This research demonstrates that a maqasid-based reading of hadith offers a balanced interpretative framework that preserves textual authority while ensuring legal relevance across changing social realities.